Yuval Sharon’s “Twilight: Gods” (2020-21): Site-Specific Reimaginations of Richard Wagner’s “Götterdämmerung” (Sound Stage Screen, 2023)
Yuval Sharon’s Twilight: Gods is a drive-through opera that presents a contemporary vernacular reimagination of Richard Wagner's Götterdämmerung. Motivated by pandemic-related concerns, it was staged in the Detroit Opera House Parking Center in October 2020 and subsequently in Chicago’s Millennium Lakeside Parking Garage in April 2021. Rejecting immersion, my article puts forth re-enchantment as a phenomenological model, which captures the sense of play underlying site-specific opera. I build on Carolyn Abbate’s notion of “ludic distance” in positing that re-enchantment is derived not despite, but because of our hyperawareness of the creative tensions present in the hybrid media and technologies fleshed out before us. Moving on then to more specifically ideological—and ethical—considerations, I interrogate the racialized scripting underpinning the opera’s display culture. Employing Matthew Morrison’s Blacksound, I examine Scene 4 (“Siegfried’s Funeral March”) in demonstrating how it reveals an attempt to muster Detroit/Blacksound in the commodified packaging of Black signifiers for the edification of an elite, mostly white audience. A musical collaboration premised on “fitting” Black music into the dominant Western paradigm perpetuates musical essentialism. Similarly problematic questions ensue from examining the ethics and politics of collaboration with the two Black poets who contribute to the productions in uneven ways. It is an open question whether, in the end, the creative team has succeeded in fulfilling the redemptive terms it has set for itself. I conclude by stimulating further questions and reflections on how a socially progressive and anti-Racist opera would look and sound like in 21st-century America.
Keywords: Twilight: Gods; Yuval Sharon; Richard Wagner; site-specific reimagination; Götterdämmerung